Characterization of beta2 (CD18) integrin phosphorylation in phorbol ester-activated T lymphocytes. - Valmu, L (1999)
Integrins are transmembrane proteins involved in cell-cell and cell-extracellular-matrix interactions. The affinity and avidity of integrins for their ligands change in response to cytoplasmic signals. This 'inside-out' activation has been reported to occur also with beta2 integrins (CD18). The beta2 integrin subunit has previously been shown to become phosphorylated in T lymphocytes on cytoplasmic serine and the functionally important threonine residues after treatment with phorbol esters or on triggering of T-cell receptors. We have now characterized the phosphorylation of beta2 integrins in T-cells in more detail. When T-cells were activated by phorbol esters the phosphorylation was mainly on Ser756. After inhibition of serine/threonine phosphatases, phosphorylation was also found in two of the threonine residues in the threonine triplet 758-760 of the beta2 cytoplasmic domain. Activation of T-cells by phorbol esters resulted in phosphorylation in only approx. 10% of the integrin molecules. Okadaic acid increased this phosphorylation to approx. 30% of the beta2 molecules, assuming three phosphorylation sites. This indicates that a strong dynamic phosphorylation exists in serine and threonine residues of the beta2 integrins.